2021
DOI: 10.3390/jpm11020081
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced Ultrasonography in the Diagnosis and Treatment Modulation of Breast Cancer

Abstract: The aim of this paper is to highlight the role of contrast-enhanced ultrasound in breast cancer in terms of diagnosis, staging and follow-up of the post-treatment response. Contrast-enhanced ultrasound (CEUS) is successfully used to diagnose multiple pathologies and has also clinical relevance in breast cancer. CEUS has high accuracy in differentiating benign from malignant lesions by analyzing the enhancement characteristics and calculating the time-intensity curve’s quantitative parameters. It also has a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 69 publications
(48 reference statements)
0
13
0
Order By: Relevance
“…The value of CEUS in the diagnosis and evaluation of the curative effect of breast cancer has been recognized ( 23 , 24 ). Our research revealed that malignant neoplasms usually showed high heterogeneous enhancement, unclear enhancement boundary, perfusion defect, perforating vessels, large post-enhanced area, and high PI and tAUC values.…”
Section: Discussionmentioning
confidence: 99%
“…The value of CEUS in the diagnosis and evaluation of the curative effect of breast cancer has been recognized ( 23 , 24 ). Our research revealed that malignant neoplasms usually showed high heterogeneous enhancement, unclear enhancement boundary, perfusion defect, perforating vessels, large post-enhanced area, and high PI and tAUC values.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal blood perfusion or blood vessel filing patterns observed on CEUS images and videos could reveal perfusion characteristics associated with malignant tumors. Studies on the role of CEUS in the past decade have shown that CEUS could increase the specificity of conventional US (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Image quality in the detection of breast cancer using SHF-CEUS is limited by insu cient signal generation from microbubbles released at high frequencies from linear transducers(18). Per uorobutane (PFB) has been shown to have a high resonance frequency and stable outer shell and can resist acoustic pressure, leading to increased microbubble oscillations that minimize collapse and loss of signal (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%